Influence of photodynamic therapy on bond strength and adhesive interface morphology of MTA based root canal sealer to different thirds of intraradicular dentin - Banci, H. A. [UNESP]; Strazzi-Sahyon, H. B. [UNESP]; Duarte, M. A.H.; Cintra, Luciano Tavares Angelo [UNESP]; Gomes Filho, João Eduardo [UNESP]; Chalub, L. O. [UNESP]; Berton, S. A. [UNESP]; de Oliveira, V. H.D. [UNESP]; Santos, Paulo Henrique dos [UNESP]; Araújo, Gustavo Sivieri de [UNESP] (Elsevier, 2020)
Background: Photodynamic therapy (PDT) is used as an adjunct to endodontic treatment to enhance microbial reduction in the root canal system. However, studies evaluating the impact of PDT on the bond strength of the canal sealer to intraradicular dentin are scarce. Thus, this in vitro study aimed to evaluate the influence of photodynamic therapy with methylene blue (MB) photosensitizer (PS) on the bond strength and morphology of the interface between mineral trioxide aggregate (MTA) based endodontic sealer and different thirds of intraradicular dentin. Methods: Fifty-five bovine incisors were used to simulate experimental endodontic treatments. Biomechanical instrumentation was performed in all root canals and teeth were divided into 5 groups (n = 11): deionized water (control), methylene blue 50 mg/L (MB50WL), methylene blue 100 mg/L (MB100WL), methylene blue 50 mg/L + red laser (MB50L), and methylene blue 100 mg/L + red laser (MB100L). The push-out bond strength of canal sealer to intraradicular dentin was measured using a universal testing machine (n = 8). Representative scanning electron microscopy images were obtained to qualify the fracture patterns. Images of the adhesive interface morphology were obtained using confocal laser scanning microscopy (n = 3). The Kruskal-Wallis test was used to compare data on bond strength between groups, and the Friedman test between thirds (α = 0.05). Results: When comparing root thirds for the MB group with the higher concentration activated by red laser, higher bond strength values was found for the apical third than for the middle third (P = 0.0302). MB in different concentrations, activated by red laser or not, had no influence on the bond strength of distinct thirds of the intraradicular dentin (P > 0.05). As for the adhesive interface morphology, the MB100L group showed a lower qualitatively sealer penetration into the intraradicular dentin. Conclusions: PDT with MB PS at 50 mg/L had no negative impact on the bond strength of MTA Fillapex canal sealer to intraradicular dentin, being a suitable antisepsis protocol for endodontic treatments.
Keywords: Bond strength; Dentin; Endodontic sealer; Methylene blue; Photodynamic therapy